Pengembangan SIG berbasis Web Sebagai Decission Support System (DSS) untuk Manajemen Jaringan Jalan di Kabupaten Aceh Timur - Jumadi, J; Muttaqin, M (Forum Geografi, 2010)
This research aims to develop a web-based GIS that can be used as a decision support system in managing the road network in East Aceh district. In this case, MySQL is used as a spatial database management system and Scalable Vector Graphics (SVG) is used as the technology to visualize spatial data in web programming. Therefore, it is expected can make geo-database application that can be distributed widely to related user. Stages of development of the system used in this study refers to the waterfall model. The order of execution of the study is divided into five stages include: early stage research, web GIS design stage, the stage of data collection, web GIS development phase and implementation phase. Data used in this study include primary and secondary data. Primary data consists of spatial and attribute data of road network (lines) and bridges (points) taken through surveys with Global Positioning System (GPS). Secondary data used include base maps derived from maps of the Rupa Bumi Indonesia (RBI) 1:25.000 scale area of East Aceh Regency. The unit of analysis used was the Locational referencing system that is defining a road network using the ânodeâ and âsectionâ. The results of this study showed that implementation of the SVG generated by PHP is able to produce a superior display vector and dynamic so it is easy to analyze. These capabilities combined with MySQL capabilities in spatial analysis and queries on RDBMS database is able to produce applications that are capable of supporting the activities of decision-making in the management of roads and bridges.